Agronomic performance of maize cultivars representing three decades of breeding in the Guinea Savannas of West and Central Africa - Kamara, A.Y.; Menkir, A.; Fakorede, M.A.B.; Ajala, S.O.; Badu-Apraku, Baffour; Kureh, I. (2004)
Maize improvement at the International Institute of Tropical Agriculture (IITA), which began in the 1970s, built on the germplasm and experience of earlier years. The main breeding emphasis was to develop maize cultivars and hybrids with high yield potential and durable resistance to diseases and pests with specific adaptation to the different agro-ecological zones of West and Central Africa. Over the years, open-pollinated cultivars have been developed with different levels of resistance to biotic and abiotic stresses. Identification of the factors that contributed to improvements in the maize cultivars developed during the past decades may be useful to sustain the genetic gain from selection in the future. A study was conducted to quantify genetic gains in yield and associated traits of open pollinated maize cultivars released from 1970 to 1999 in the West African savannas. The genetic gain in grain yield was 0·41% per year and seems to be associated with increases in total biomass and kernel weight, and reductions in plant height and days to flowering (anthesis and silking). There was no significant change in harvest index of the cultivars.